Traveling Wave Vibration and Experimental Analysis of the Diaphragm Disc Sun-gear Shaft of High-speed Planetary Gearbox - Wang Xiaopeng; Liu Shijun (Jixie chuandong, 2020)
The simulation model of the diaphragm disc sun-gear shaft of high-speed planetary gearbox is established.Based on the design principle of the floating structure of sun-gear shaft in planetary gearbox，three conditions including free-free，simple support-axial and simple support-fixed support are drawn up.The natural frequency and traveling wave vibration of sun-gear shaft were investigated，and the corresponding diagrams of mode of vibration and Campbell figure are drawn later.A gearbox test bench is built for experimental analysis.The result shows that when the main mode of sun-gear shaft with deformation of gear teeth resonates with one-fold frequency，the excitation force has largest amplitude，the two and three times followed.The vibration forms of teeth are torsional vibration，traveling wave vibration and bending vibration.A wide range of resonance points is produced between diaphragm or barrel shaft and multiple frequency of shaft.The resonance response is smaller by the greater multiple frequency of shaft.The experimental shows that during the process of increasing the speed from zero to working speed，the vibration value fluctuates significantly and then decreases to stable quickly，which indicates that the vibration of system is not expanded by exciting force and the influence on system stability is smaller.The geometric design of sun-gear shaft has a certain rationality and applicability.